Quantitativity in the Russian and Chinese Languages: Numerals - O V Lazareva (RUDN Journal of Language Studies, Semiotics and Semantics, 2015)
The article reviewed is devoted to the linguistic representation of the grammatical category of quantity through comparing grammatical techniques applied to express the meaning both in the Russian and Chinese languages.